Odpowiedzi

Najlepsza Odpowiedź!
2010-03-27T20:56:56+01:00
A) x + 5 = 10
x=10-5
x=5

b) 2x + 3 = 15
2x = 15-3
2x = 12 / :2
x = 6

c) 5x + 13 =23
5x = 23-13
5x = 10 / : 5
x = 2

d) 3x + 11 = 41
3x = 41-11
3x = 30 / :3
x = 10

e) - x + 2 = 8
-x = 8-2
-x = 6 / :(-1)
x = -6

f) - x + 5 = - 2
-x = -2-5
-x = -7 / :(-1)
x = 7

g) - 2x - 7 = 11
-2x = 11+7
-2x = 18 / :(-2)
x = -9

h) - 5x + 3 = -12
-5x = -12-3
-5x = -15 / :(-5)
x = 3
110 4 110
2010-03-27T21:00:02+01:00
A) x + 5 = 10/-5
x=5

b) 2x + 3 = 15/-3
2x=12/:2
x=6

c) 5x + 13 =23/-13
5x=10/:5
x=2

d) 3x + 11 = 41/-11
3x=30/:3
x=10

e) - x + 2 = 8/-2
-x=6/*(-1)
x=-6

f) - x + 5 = - 2/-5
-x=-7/*(-1)
x=7

g) - 2x - 7 = 11/+7
-2x=18/:(-2)
x=-9

h) - 5x + 3 = -12/-3
-5x=-15/:(-5)
x=3
25 3 25
2010-03-27T21:01:20+01:00
A) x + 5 = 10
x = 10 - 5 = 5
b) 2x + 3 = 15
2x = 15 - 3 = 12
x = 12/2 = 6
c) 5x + 13 =23
5x = 23 - 13 = 10
x = 10/5 = 2
d) 3x + 11 = 41
3x = 41 - 11 = 30
x = 30/3 = 10
e) - x + 2 = 8
- x = 8 - 2
- x = 6
x = - 6
f) - x + 5 = - 2
- x = - 2 - 5
- x = - 7
x = 7
g) - 2x - 7 = 11
- 2x = 11 + 7
- 2x = 18
x = - 18/2 = - 9
h) - 5x + 3 = -12
- 5x = - 12 - 3
- 5x = - 15
x = 15/5 = 3
62 4 62
Komentarz został usunięty